Structural Characteristics of Lignite Char from Different Pyrolysis Reactors and the Influence on Their Gasification Reactivity - Zhang,Ying (2022)
The gasification reactivity of coal char is affected by numerous experimental variables, and char structure is one of the dominant factors. In this work, Raman spectroscopy, powder X-ray diffraction (XRD), and N2 adsorption were used to investigate the physical and chemical structure of char prepared under different pyrolysis conditions. Three kinds of pyrolysis reactors, fluidized-bed reactor (FL), entrained-flow-bed reactor (EF), and fixed-bed reactor (PT), were designed and used to prepare the char samples. Lignite was pyrolyzed in a fixed-bed reactor with a heating rate of 10 ºC min-1, and the final temperature was 1000 ºC. The gasification reactivity of char was characterized in a quartz fixed-bed reactor under CO2, H2O, and their mixtures at 750 ºC. FB reactor produces chars with a smaller interlayer spacing of aromatic layers (d002), and FL reactor produces chars with a larger mean crystallite size along the c-axis (Lc) and aromaticity (ƒa) but inhibits the growth of mean crystallite size along the a-axis (La). The content of small aromatic rings, which is higher in the FL reactor, positively affects the initial intrinsic reactivity.